Anthanthrene dye-sensitized solar cells: influence of the number of anchoring groups and substitution motif. Issue 119 (19th November 2015) - Geng, Yan; Yi, Chenyi; Bircher, Martin Peter; Decurtins, Silvio; Cascella, Michele; Grätzel, Michael; Liu, Shi-Xia
Abstract : Four anthanthrene-based molecules were synthesized as sensitizers in dye-sensitized solar cells, leading to the best overall efficiency up to 5.3%. Abstract : Four new dye molecules comprising an anthanthrene core, thiophene-cyanoacrylic acid electron acceptor and triphenylamine (TPA) electron donor units were prepared. Thereby, the substitution pattern at the anthanthrene core has been varied systematically. The molecules were fully characterized using optical spectroscopy and cyclic voltammetry, and their electronic structures and excitation energies were calculated by DFT and TDDFT methods. The photovoltaic properties of dye-sensitized solar cells based on these molecules were investigated. In comparison to symmetric dyes, the introduction of the organic donor TPA in asymmetric dyes leads to a remarkable improvement of the solar energy conversion efficiencies due to higher V oc and J sc values of devices, giving rise to the best overall efficiency of 5.27%.